2020
DOI: 10.1002/marc.202000392
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Polymeric Interface by Janus Nanosheet

Abstract: A strategy is proposed to stabilize the polymeric interface by using the irregular Janus nanosheet (JNS). The poly(vinylidene fluoride) (PVDF)/poly(l‐lactic acid) (PLLA) at 60/40 (wt/wt) with a bi‐continuous structure is selected as the model melt blend, and the PMMA/epoxy JNS is synthesized and used as the compatibilizer. The JNS is preferentially located at the interface. The interfacial coverage by the JNS reaches a saturated state forming the interconnected jamming structure at 0.5 wt% of the JNS. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Compared with other PLA/PBS composites in previous studies, , our composites have distinct superiority in both mechanical performance and oxygen barrier properties. As shown in Figure e, the PLA/PBS composites compatibilized by clay 30 exhibit an oxygen barrier property of (1.7–2.3) × 10 –14 cm 3 cm·cm –2 ·s –1 ·Pa –1 .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with other PLA/PBS composites in previous studies, , our composites have distinct superiority in both mechanical performance and oxygen barrier properties. As shown in Figure e, the PLA/PBS composites compatibilized by clay 30 exhibit an oxygen barrier property of (1.7–2.3) × 10 –14 cm 3 cm·cm –2 ·s –1 ·Pa –1 .…”
mentioning
confidence: 93%
“…Janus materials (JMs) integrate the Pickering effect of solid colloids and amphiphilicity of surfactant, , providing a multifunctional platform in the polymer blending field along with their versatile delicate modification capabilities. , Previous research has proved that JMs can serve as highly effective compatibilizers in immiscible polymer blends. JMs will eventually anchor at the phase interface due to their affinity to both polymers and high desorption energy from the interface, which is several orders of magnitude higher than thermal energy. Recently, we have reported that EP/LNBR JNs can effectively compatibilize the EP/LNBR blend by covalent bonding at the interface of the blend . Besides, the silica-based Janus nanosheets (PMMA/epoxy JNs) have also been fabricated and investigated, which can serve as compatibilizers for stabilizing the interface of a bicontinuous poly­( l -lactic acid)/poly­(vinylidene fluoride) (PLLA/PVDF) blend . Both JNs in the above two systems share the same merits that they can jam at the interface of blend, which could lead to the extremely low threshold in the composites for efficient compatibilization.…”
mentioning
confidence: 97%
“…For example, when the PI-SiO 2 @PDVB-PB (PI: polyisoprene, PDVB: polydivinylbenzene, PB: polybutadiene) JPs or PS-silica-PI (PS) Janus nanosheets were used to compatibilize PI/PB or PS/PI blends, respectively, the discrete domain sizes decreased significantly. , In addition, irregular Janus nanosheets have been used to stabilize the morphologies of polymeric domains by forming jamming structures . The refinement and stabilization of dispersed domains produced by the compatibilization of JPs will contribute to the improvement of mechanical properties and conductivity of the blends at a low threshold. Moreover, the Janus nano-micelles or NPs with PMMA and poly­( l -lactide) (PLLA) chains were also synthesized by “grafting through” or “grafting onto” method and the in-situ reactive melt blending, further being employed to compatibilize poly­(vinylidene fluoride) (PVDF)/PLLA (PVDF) blends. In these studies, the Janus materials were mainly used to create a more compatible interface of the immiscible blends by grafting polymer molecules with preferable blend component compatibility utilizing the complex grafting processes.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 In addition, irregular Janus nanosheets have been used to stabilize the morphologies of polymeric domains by forming jamming structures. 31 The refinement and stabilization of dispersed domains produced by the compatibilization of JPs will contribute to the improvement of mechanical properties 32 and conductivity of the blends 31 at a low threshold. Moreover, the Janus nano-micelles or NPs with PMMA and poly(L-lactide) (PLLA) chains were also synthesized by "grafting through" or "grafting onto" method and the in-situ reactive melt blending, further being employed to compatibilize poly(vinylidene fluoride) (PVDF)/PLLA (PVDF) blends.…”
Section: Introductionmentioning
confidence: 99%
“…They further investigated the effect of JPs on the morphology of blends and found that JPs can better improve the PPE/SAN compatibility than the SBM copolymer, which is manifested in the improvement of morphology homogeneity and reduction of the phase domain size . Yang et al stabilized the poly­(vinylidene difluoride)/poly­( l -lactic acid) (PVDF/PLLA) interface using PMMA/epoxy Janus nanosheets (JNs). The blend interface was covered by JNs forming a cocontinuous structure at 0.5 wt % of JNs, and the interface is thus stabilized and well preserved after annealing at a high temperature.…”
Section: Introductionmentioning
confidence: 99%